OPTIMALISASI PELAYANAN UNIT BPJS RSUD MELALUI PERHITUNGAN WAKTU SIKLUS OPERATOR PELAYANAN SEP - Cukri Rahma; Angga Ariska; Villa Afriasari (Universitas Teuku Umar, 2018)
Now, industry that is engaged in services has increased, this requires the procurement of services must be able to provide optimal service. The business is needed for the company to remain competitive in other service industries. One of the main factors that greatly influences how services are provided. The quality of production is very dependent on the efficient use of time. Measurement of work time can be seen from the production and operating activities in the company whether efficient or not. The more effective and efficient the employee completes a work cycle, the more productive and the resulting output will be as high. Cut Nyak Dhien Regional Hospital is a company engaged in the field of health supply. Cutnyak Dhien Regional Hospital has one service unit, one of which is the Health BPJS unit, where the SEP card (patient eligibility letter) is prepared in this unit. This SEP will be brought to certain poly-poly. The problem found was that operators had to complete SEP for almost an average of five hundred patients per day. Therefore it is necessary to calculate the work time needed to complete the SEP. One way to measure how much work time is needed by an operator in making an SEP is to calculate the cycle time of the SEP manufacturing process. Cycle time is one way to find out the operator's working time in the technique of measuring work time. Measurements were made directly using stop-hours. The measurement was repeated three times with 10 observations for each operator. The measurement results show that the operator can complete SEP within the normal timeframe of around 50 to 70 seconds per patient.